Performance improvement of piezoelectric energy harvester using non-uniform beam with cavity. (17th February 2019) - Raju, S. Srinivasulu; Umapathy, M.; Uma, G.
Abstract: Energy harvesting using cantilever based piezoelectric structure is most popular for harvesting electrical energy from ambient vibrations. Attempts are also made to increase the harvester power by means of tailoring the structural parameters of the cantilever beam. This paper presents a non-uniform beam based energy harvester associated with a piezoelectric patch to achieve higher power by means of tailoring the width of beam linearly with positive tapering ratio towards its free end. It is also proposed to introduce a rectangular and trapezoidal cavity in the uniform thickness-width tapered energy harvesters to further maximise the harvester voltage. The mode shapes and fundamental natural frequency of proposed energy harvesters are obtained analytically by using Euler-Bernoulli beam theory and its free vibration solution is analysed by using Bessel functions. The performance of the proposed energy harvesters is demonstrated through both analytical and experimental implementation. It is shown that the inclusion of the rectangular and trapezoidal cavity in the harvester beam significantly affects the output voltage due to the change in the neutral axis of beam. The effects of variation in thickness of rectangular and trapezoidal cavity on the mode frequencies, harvester voltage and power are determined analytically. From the results of analytical model and experimentation, it is concluded that width tapered beam increases the harvester voltage by 16.33% as compared to the energy harvester considered with uniform cantilever beam. Among all the energy harvesters projected during this paper, the maximum voltage is produced from the width tapered beam with trapezoidal cavity. The experimental results are in close agreement with the results obtained from the analytical model.